The democracy deficit of corporate social responsibility in postneoliberal times: An analysis of the Argentinian and Ecuadorian experiences - Cisneros, Paúl (2014)
Several evaluations of contemporary left-of-center governments in South America suggest that natural resource governance in the region has become post-neoliberal only in the sense that States augmented the appropriation and distribution of rent motivated by sustained international demand for commodities. The political ecologies of mining remain characterized by increasing demands for more democratic decision-making as occurred in the 1990s. In order to explain this continuity, most studies focus on the interactions between States and civil societies. They state that a pragmatic stance on resource governance regards rent capture and distribution over the development of mechanisms for inclusion in decision-making. These assessments give only a partial account of the interactions involved in such dynamic, they underestimate corporate behavior as a central component of emerging forms of governance. We argue that companies were central actors of the production of mining conflicts during the 1990s and still exert an important degree of influence in resource governance through corporate social responsibility (CSR) strategies. Our findings show that since the neoliberal legal and administrative reforms of the early 1990s, Argentinian and Ecuadorian governments have supported a system of mining governance that regards the economic interests over the demands for more democratic decision-making. Nevertheless, even after recognizing the deleterious effects of neoliberal CSR practiced by companies, left-of-center governments have not been able to steer corporate behavior in a new direction.